Dhx15 regulates zebrafish definitive hematopoiesis through the unfolded protein response pathway. Issue 9 (11th July 2021) - Cai, Yuanhua; Wang, Jing; Jin, Daqing; Liu, Qiao; Chen, Xianglei; Pan, Lili; Li, Yang; Wang, Xuechun; Qian, Feng; Wang, Jiucun; Zhong, Tao Peter; Wang, Shaoyuan
Abstract: Gene alterations are recognized as important events in acute myeloid leukemia (AML) progression. Studies on hematopoiesis of altered genes contribute to a better understanding on their roles in AML progression. Our previous work reported a DEAH box helicase 15 (DHX15) R222G mutation in AML patients, and we showed DHX15 overexpression is associated with poor prognosis in AML patients. In this work, we further study the role of dhx15 in zebrafish developmental hematopoiesis by generating dhx15 −/− zebrafish using transcription activator‐like effector nuclease technology. Whole‐mount in situ hybridization (WISH) analysis showed hematopoietic stem/progenitor cells were dramatically perturbed when dhx15 was deleted. Immunofluorescence staining indicated inhibited hematopoietic stem/progenitor cell (HSPC) proliferation instead of accelerated apoptosis were detected in dhx15 −/− zebrafish. Furthermore, our data showed that HSPC defect is mediated through the unfolded protein response (UPR) pathway. DHX15 R222G mutation, a recurrent mutation identified in AML patients, displayed a compromised function in restoring HSPC failure in dhx15 −/− ; Tg (hsp: DHX15 R222G) zebrafish. Collectively, this work revealed a vital role of dhx15 in the maintenance of definitive hematopoiesis in zebrafish through the unfolded protein respone pathway. The study of DHX15 and DHX15 R222G mutation could hold clinical significance for evaluating prognosis of AML patients with aberrant DHX15 expression. Abstract : Dhx15 is essential for hematopoietic stem/progenitor cell (HSPC) development in zebrafish; HSPC failure is mediated by the unfolded protein response (UPR) pathway in dhx15 −/− zebrafish.